A Trigger-Tool-based Description of Adverse Events in Helicopter Emergency Medical Services in Qatar - Heuer, Calvin (Division of Emergency Medicine, 2022)
Introduction Adverse Events (AEs) in Helicopter Emergency Medical Services (HEMS) remains poorly reported, despite the potential for harm to occur. The Trigger Tool (TT) represents a novel approach to AE detection in healthcare. The aim of this study was to retrospectively describe the frequency of AEs and their Proximal Causes (PCs) in Qatar HEMS. Methods Using the Pittsburgh Adverse Event Tool (PittAETool) to identify AEs in HEMS, we retrospectively analyzed 804 records within an existing AE TT database (21-month period). We calculated outcome measures for Triggers, AEs, and Harm per 100 patient encounters, plotted measures on Statistical Process Control (SPC) charts, and conducted a multivariate analysis to report harm associations. Results We identified 883 Triggers in 536 patients, with a rate of 1.1 Triggers per Patient Encounter, where 81.2% had Documentation Errors (n=436). An AE and Harm rate of 27.7% and 3.5% respectively was realized. The leading PC was Actions by HEMS Crew (81.6%; n=182). The majority of harm (57.1%) stemmed from the Intervention and Medication triggers (n=16), where Deviation from Standard of Care was common (37.9%; n=11). Age and diagnosis adjusted odds was significant in the Patient Condition (6.50; 95% CI, 1.71-24.67; P= 0.01) and Interventional (11.85; 95% CI, 1.36-102.92; P= 0.03) trigger groupings, while age and diagnosis had no effect on Harm. Conclusion The TT methodology is a robust, reliable, and valid means of AE detection in the HEMS domain. Whilst an AE rate of 27.7% is high, more research is required to understand prehospital clinical decision-making and reasons for guideline deviance. Furthermore, focused quality improvement initiatives to reduce AEs and Documentation errors should also be addressed in future research.